Corporate Responsibilities Related to Pharmaceutical Industry Compliance in the Use of Test Animals in Indonesia - Ramadhanti, Shaila Azalea; Sakti, Muthia (UNIVERSITAS PAKUAN, 2025)
Abstract This study aims to analyze corporate responsibility in ensuring the compliance of the pharmaceutical industry with regulations governing the use of laboratory animals in Indonesia, emphasizing aspects of legal, ethical, and technical adherence to animal welfare principles. This study adopts normative juridical research method employing both statuory and conceptual approaches. The data were gathered through library research, comprising primary legal materials for instance like laws and regulations, additionally secondary legal materials including books, journal articles, as well as online references. The findings indicate that although Indonesia has established several regulations such as Law No. 18 of 2009 jo. No. 41 of 2014, Government Regulation No. 95 of 2012, Minister of Health Regulation No. 75 of 2020, and BPOM Regulations No. 10 of 2022 and No. 20 of 2023, their implementation within the pharmaceutical industry remains suboptimal due to weak enforcement and monitoring mechanisms. Therefore, the establishment of an integrated compliance system combined with ethical and technical oversight is essential to ensure that the use of laboratory animals is conducted transparently, responsibly, and in accordance with the 3R and 5F principles. Keywords: laboratory animals, legal compliance, animal welfare.